Deposit Insurance Schemes Around the World – Comparative Analysis - Dadej, Mateusz (Journal of Finance and Financial Law, 2018)
The purpose of this article is to show and compare various types or arrangements, adopted around the world and their implications on financial system. The article presents theoretical aspects of deposit insurance schemes functioning, which gives rudiments for reader to judge different arrangements shown in further part of the article. In this article, author characterized various features, such as : formalization, structure and administration, limit of deposit coverage, funding and also its role. Every description is presented with economic issue that given arrangement is related to and contains examples of countries where it exists. Empirical data is taken from World Bank dataset and IADI, in many cases updated with information from official websites or documents of deposit guarantee schemes or institutions that are responsible for them and working papers.